IMPLEMENTATION OF INTERNAL CONTROL SYSTEM ON AVIAN PT.AVIA SIDOARJO VIEWED FROM THE QUALITY OF HUMAN RESOURCES - Nafidah, Lina Nasihatun (Entrepreneur, 2011)
AbstractEffective implementation of each company's internal control system is greatly influenced by the quality of human resources who implement them. No matter how well a system will be wasted just like that, if not supported by adequate human resources quality. Particularly the personal qualities of human resources consisting of education, experience and relevant training. This study aims to determine the effect of quality human resources to the implementation of internal control system on PT. Avia Avian Sidoarjo. Results obtained from this study is that the Education and Training have a significant effect on the implementation of Internal Control System, while the experience of no significant impact on the Implementation of Internal Control System.Keywords: Education, Experience, Training and Implementation of Internal Control System.AbstrakPelaksanaan yang efektif dari sistem pengendalian internal masing-masing perusahaan sangat dipengaruhi oleh kualitas sumber daya manusia yang melaksanakannya. Tidak peduli seberapa baik sistem akan sia-sia begitu saja, jika tidak didukung oleh kualitas sumber daya yang memadai manusia. Terutama kualitas pribadi sumber daya manusia yang terdiri dari pendidikan, pengalaman dan pelatihan yang relevan. Penelitian ini bertujuan untuk mengetahui pengaruh kualitas sumber daya manusia dengan pelaksanaan sistem pengendalian intern pada PT. Avia Avian Sidoarjo. Hasil yang diperoleh dari studi ini adalah bahwa Pendidikan dan Pelatihan memiliki pengaruh yang signifikan pada pelaksanaan Sistem Pengendalian Intern, sementara pengalaman tidak berpengaruh signifikan terhadap Pelaksanaan Sistem Pengendalian Intern.Kata kunci: Pendidikan, Pengalaman, Pelatihan dan Pelaksanaan Sistem Pengendalian Intern.